Effects of aminoethoxyvinylglycine treatments on pre-harvest fruit drop and fruit quality of Braeburn apples - Ozturk, Burhan; Yildiz, Kenan; Ozkan, Yakup; Kilic, Kemal (Bangladesh Journal of Botany, 2018)
This study was conducted to determine the effects of increasing aminoethoxyvinylglycine (AVG) concentrations on pre-harvest drop and fruit quality parameters of ‘Braeburn’ apples. Results revealed that AVG treatments increased the fruit removal force and significantly decreased pre-harvest drops compared to control treatment. AVG was found to be more effective in controlling pre-harvest drops than naphthaleneacetic acid (NAA). There were significant differences among AVG doses with regard to preharvest drop rates. The lowest ratio of pre-harvest drop was observed in 400 mg/l AVG treatment. All AVG doses decreased ethylene biosynthesis. Inhibition of ethylene biosynthesis was higher in 300 and 400 mg/l AVG treatments than the other AVG treatment. AVG retarded fruit ripening of ‘Braeburn’ apples. Measurements, performed at different dates of ripening process, revealed higher flesh firmness values for AVG-treated fruits than the control. Starch degradation was delayed by AVG treatments. Effects of AVG on fruit peel color varied with years. While significant effects of AVG treatments on peel color were not observed in the first year, especially higher AVG doses significantly increased L* values and hue angles in the second year. AVG treatments also significantly increased fruit mass in both years. Significant changes in fruit geometric diameters were not observed with AVG treatments, except for 300 mg/l AVG treatment of second year.